SCHOOL OF THOUGHT OF SUCKLINGS TECHNOLOGISTS AND ITS CREATOR – PROFESSOR M. I. KNYGA - Тендітник, В. С. (Scientific Progress & Innovations, 2014)
Some research job results of Professor Moisey Ivanovich Kniga and his students are performances, to the suckling productivity of cows directed on an increase and improvement of quality of milk and sucklings products. A creator of Kharkov scientific school of sucklings technologists of M. I. Kniga is the indeed real eminent Scientist and unselfish Teacher. Together with his students he brought in a considerable contribution to development of science about a dairying and technology of milk and sucklings products. He was a eminent organizer and leader of one of leading agricultural institutes of higher – Kharkov Zoological and Veterinary Institute.